Developmental trajectories of Body Mass Index from infancy to 18 years of age: prenatal determinants and health consequences - Ziyab, Ali H (BMJ Publishing Group, 2014)
BACKGROUND: Knowledge on the long-term development of adiposity throughout childhood/adolescence and its prenatal determinants and health sequelae is lacking. We sought to (1) identify trajectories of Body Mass Index (BMI) from 1 to 18 years of age, (2) examine associations of maternal gestational smoking and early pregnancy overweight with offspring BMI trajectories and (3) determine whether BMI trajectories predict health outcomes: asthma, lung function parameters (forced expiratory volume in one second (FEV(1))/forced vital capacity (FVC) ratio), and blood pressure, at 18 years. METHODS: The Isle of Wight birth cohort, a population-based sample of 1456 infants born between January 1989 and February 1990, was prospectively assessed at ages 1, 2, 4, 10 and 18 years. Group-based trajectory modelling was applied to test for the presence of latent BMI trajectories. Associations were assessed using log-binomial and linear regression models. RESULTS: Four trajectories of BMI were identified: ‘normal’, ‘early persistent obesity’, ‘delayed overweight’, and ‘early transient overweight’. Risk factors for being in the early persistent obesity trajectory included maternal smoking during pregnancy (RR 2.16, 95% CI 1.02 to 4.68) and early pregnancy overweight (3.16, 1.52 to 6.58). When comparing the early persistent obesity to the normal trajectory, a 2.15-fold (1.33 to 3.49) increased risk of asthma, 3.2% (0.4% to 6.0%) deficit in FEV(1)/FVC ratio, and elevated systolic 11.3 mm Hg (7.1 to 15.4) and diastolic 12.0 mm Hg (8.9 to 15.1) blood pressure were observed at age 18 years. CONCLUSIONS: Maternal prenatal exposures show prolonged effects on offspring's propensity towards overweight-obesity. Distinct morbid BMI trajectories are evident during the first 18 years of life that are associated with higher risk of asthma, reduced FEV(1)/FVC ratio, and elevated blood pressure.